2015
DOI: 10.1371/journal.pone.0143483
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Genomics with Nutrition Models to Improve the Prediction of Cattle Performance and Carcass Composition under Feedlot Conditions

Abstract: Cattle body composition is difficult to model because several factors affect the composition of the average daily gain (ADG) of growing animals. The objective of this study was to identify commercial single nucleotide polymorphism (SNP) panels that could improve the predictability of days on feed (DOF) to reach a target United States Department of Agriculture (USDA) grade given animal, diet, and environmental information under feedyard conditions. The data for this study was comprised of crossbred heifers (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Because many factors inherent to the genetic makeup of the animal affect its composition of gain, the incorporation of nutrition with a genetic predisposition may likely advance the modeling and simulation of growth biology. Tedeschi (2015) provided a preliminary modeling approach to combine a nutrition and growth model with molecular breeding values obtained from commercial, single-nucleotide polymorphism panels. The author indicated that the molecular breeding values for the ribeye area were an important piece of genetic information for increasing the precision in predicting mature weight at a given body composition.…”
Section: Extant Mathematical Models In Ruminant Productionmentioning
confidence: 99%
“…Because many factors inherent to the genetic makeup of the animal affect its composition of gain, the incorporation of nutrition with a genetic predisposition may likely advance the modeling and simulation of growth biology. Tedeschi (2015) provided a preliminary modeling approach to combine a nutrition and growth model with molecular breeding values obtained from commercial, single-nucleotide polymorphism panels. The author indicated that the molecular breeding values for the ribeye area were an important piece of genetic information for increasing the precision in predicting mature weight at a given body composition.…”
Section: Extant Mathematical Models In Ruminant Productionmentioning
confidence: 99%
“…With the advancements in the Precision nutrition of ruminants identification of single nucleotide polymorphism panels, specific molecular breeding values have been computed for relevant traits for the beef cattle industry. The integration of nutrition models and genomics has been conceptualised and reported to improve the predictability of deposition of carcass fat and protein in growing cattle (Tedeschi, 2015). In addition, new sensor technologies show great potential to inform both animal nutrition models and genetic predictions, as these can facilitate the collection of phenotypic data (Greenwood et al, 2016), and increase their accuracy such as in the case of X-ray body scanners for automated measurements of carcass composition and yield (Scholz et al, 2015).…”
Section: Simulation Modelling: the Role Of Ruminant Nutrition Modelsmentioning
confidence: 99%
“…Oltjen et al (2000) integrated genetic parameters (breeding value) into a growth model Oltjen et al, 1986;Soboleva et al, 1999). Recently, Tedeschi (2015) used SNP panels to improve the predictability of days on feed to reach desired carcass composition of growing beef cattle by the Cattle Value Discovery System . In their analysis, the inclusion of the molecular breeding value of ribeye area increased by 13% the precision to predict body weight at 28% empty body fat.…”
Section: Integrating Genomics Into Nutrition Modelingmentioning
confidence: 99%